Meningkatkan Kualitas Pelayanan Reservasi Dengan Memanfaatkan Bahasa Pemograman Sebagai Kerangka Permodelan - Rosalia, Farah; Aryanto, Joko (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Angkraaf culture and culinary cafe is a cafe located in Yogyakarta, this cafe is often visited by students. Cafe reservation is the process of ordering or providing seats at a cafe for customers who want to visit and enjoy cafe services. In an era where busy and fast-paced lifestyles are becoming increasingly common, cafe reservations have become an essential necessity for many people who want to guarantee a seat at angkraaf culture and culinary cafes. The current cafe reservation process still uses the manual method which can take quite a long time. In this method, customers must contact the cafe directly by phone or come to the cafe to make a reservation. This can cause customers to have difficulty contacting the cafe when it is busy or when the cafe is closed. there is a risk of errors or overlapping reservations. Cafe staff may experience errors in recording customer information or skip incoming reservations altogether. This can result in dissatisfied customers who arrive at the cafe and find that the table they were expecting is not available. To overcome this problem, the café is considering creating a website-based cafe reservation system. By utilizing this technology, cafes can increase efficiency, increase accessibility, and provide a better reservation experience to customers.